Determinación del ruido ambiental en dos zonas del cantón Latacunga; Zona 1 (Terminal Terrestre), Zona 2 (Mercado Mayorista), de la provincia de Cotopaxi. Propuesta de control al ruido año 2022. - Mallitasig Lema, Valeria Estefania (2022)
In the current research, it was made the existing environmental noise determination into two zones from Latacunga cantón, zone 1 (terrestrial terminal) and zone 2 (Wholesale market), from Cotopaxi province. Its aims were to make the two study areas current diagnosis, to analyze the noise levels and their comparison with the current legal regulations and it was developed a proposal to mitígate environmental noise in the two study areas. The methodology was based on the deductive and inductive method application, while the quantitative methodology allowed establishing the existing noise valúes each of the localities for their subsequent comparison with the current legal regulations TULSMA and Ministerial Agreement 097 A.V The results allowed to determine, what the highest noise averages are located in the extemal points from Terrestrial Terminal with a 88.1dB average on Saturdays and in the Wholesale Market a 94.1 dB average noise on Tuesdays and Saturdays, however, all points monitored inside and outside the established Terrestrial Terminal and Wholesale Market are found above the 60dBA as the permissible limit in the environmental standard for land for commercial use during the daytime. Valúes, which allowed establishing a proposal for noise control in the Terrestrial Terminal and Wholesale Market from Latacunga Cantón, with measures applicable to the area conditions. Concluding that the noise levels in the Terminal and Wholesale Market are directly influenced by commercial activities and the transport vehicular traffic and heavy transport cooperatives, since it is located in a purely commercial area.